Factors that determine the healthy behavior of consumers. A systematic review between 2013 -2022 (LACCEI, 2024)
The objective of this study is to identify the factors that determine the healthy behavior of consumers of organic products and their supply, taking as a reference various systematic studies in recent years at a global level. The information sources used were important scientific databases such as Scopus, Ebsco, Proquest, Dialnet, Redalyc and Scielo. The following methodology was used: the type of research is a systematic review. The techniques used are the analysis, contrast, comparison of data and informative ideas for the variables established in this report. The development of the results demonstrates the analysis of the information and the collection of the systematic articles. It is concluded that within the scientific literature, consumer behavior is a highly amplified concept, which contradicts opinions regarding authors, this produces a comprehension bias. It is deduced that there are five factors that determine healthy behavior in the consumer, which intervene in the lifestyle, purchase process, customary experiences, among others. These are concluded in the following: sociocultural, socioeconomic, environmental, ethical, and external communication (marketing) factor.